Studies of silica-hybrid nanoparticles with targeting and photodynamic capabilities for the topical therapy of melanoma - Tham, Phoebe Huijun (2018)
The topical treatment of skin cancer is a better alternative to systemic therapy. This is because of the accessibility of the cancerous tissue compared to deeper tissues. However, when it comes to melanoma, the topical treatment in clinics has been restricted by the limited penetration of drugs through the skin to the melanoma site. Of the possible modes of topical treatment, photodynamic therapy is the most promising, as it offers the added advantage of selectivity of therapy. However, for melanoma, photodynamic therapy is not yet used in clinics as the approved photosensitizers are unable to permeate deep enough into the skin, and the light wavelength used to activate them is not penetrative enough to reach the melanoma site. Furthermore, the photosensitizers that can absorb at longer wavelengths tend to be strongly hydrophobic and of high molecular weight, resulting in an inability to penetrate the skin barrier. Selectivity can be further improved by adding targeting ability to the particles. For melanoma, two small molecular inhibitors, Dabrafenib and Trametinib, have been identified as targeting chemotherapeutic drugs. These very promising inhibitors, however, suffer from several drawbacks, including their low bioavailability when systemically administered. A topical approach to deliver these inhibitors would be beneficial. In order to solve the problems faced in the topical treatment of melanoma using photodynamic therapy and targeted therapy, this work explored the use of nanotechnology, in particular a class of materials called organic-inorganic hybrid mesoporous nanoparticles. This class of nanomaterials are an extension of the conventional mesoporous silica nanoparticles, in which the silica skeleton of the nanoparticle can be modified organically, giving the nanoparticle functional xiii abilities while freeing up the mesopores for additional drug loading. Such particles have not been explored for topical therapy previously. The synthesis procedure and chemicals required were first optimised. Variables such as the TMOS to PC ratio and the inhibitor ratio were studied in terms of photodynamic efficiency, and optimized. Following which, the nanoparticle was characterised in depth using various techniques. It was shown to have a good singlet oxygen quantum yield of 0.42 and excellent photostability. Its small size and surface area enables more interaction of the generated ROS with intracellular biomolecules, improving overall efficacy of photodynamic therapy, and also the permeation through skin. The final product (PcNP@Drug) was first tested in vitro against the melanoma cell lines (BRAFV600E, BRAFwt) and healthy skin cells. It was effective against BRAFV600E cells, proving its efficacy and specificity towards the targeted BRAFV600E cells, while not affecting the healthy or BRAFwt cells as much. The combination analysis was also conducted, and it was observed that photodynamic therapy and the two inhibitors worked synergistically together for the BRAFV600E mutant cells. Various assays such as live/dead, in vitro ROS generation assays were also conducted and it was shown that ROS can be generated in cells as well, and the cells could die. Subsequently, the penetration ability of PcNP@Drug was tested on full-thickness porcine skin and was observed that with the use of microneedles, the penetration was much higher than without.. The microneedle approach to topical administration has the benefit of reducing drug build-up in the epidermis, and thus minimize damage to healthy cells. The PcNP@Drug nanoplatform was then xiv tested on living mice and it was proven that the nanosystem was able to not only permeate through into the melanoma subcutaneous growths, but the combined targeted therapy and photodynamic therapy was able to inhibit tumour growth. The results obtained in this study show that this PcNP@Drug nanosystem can be used as a topical method for treating the deeper-seated malignancies in skin, with reduced damage to healthy cells, especially in conjunction with the microneedle approach.